Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri Bojong 3 Kota Tangerang - Sabdaniah, Feby; Zamroni, Moch.; Sunaryo, Sunaryo (FONDATIA, 2023)
This study aims to determine whether there is influence or not the Contextual Teaching and Learning (CTL) learning model on the science learning outcomes of fifth grade students at SDN Bojong 3 Tangerang City. This study used the Quasi Experiment method with the Nonequivalent Control Group Design. The sample studied was 62 students consisting of 31 students in the experimental class (VB) and 31 students in the control class (VA). Previously, this research instrument was given to the object of research. The instrument was tested first, namely the validity and reliability trials were proven to be valid & reliable. The study showed that the final test results of the experimental class and control class with the posttest T-test obtained tcount (4.576) > ttable (2.000) with a significant level of 0.05. So the results of this study can be concluded that there is an influence on students' science learning outcomes by using the Contextual Teaching and Learning (CTL) learning model with students who are taught by conventional learning models.